Lessons Learned about Neurodegeneration from Microglia and Monocyte Depletion Studies - Lund, Harald; Pieber, Melanie; Harris, Robert A. (Frontiers in Aging Neuroscience, 2017)
While bone marrow-derived Ly6Chi monocytes can infiltrate the central nervous system they are developmentally and functionally distinct from resident microglia. Our understanding of the relative importance of these two populations in the distinct processes of pathogenesis and resolution of inflammation during neurodegenerative disorders was limited by a lack of tools to specifically manipulate each cell type. During recent years the development of experimental cell-specific depletion models has enabled this issue to be addressed. Herein we compare and contrast the different depletion approaches that have been used, focusing on the respective functionalities of microglia and monocyte-derived macrophages in a range of neurodegenerative disease states, and discuss their prospects for immunotherapy.